Interleukin-8 and tumor necrosis factor-alpha in youth with mood disorders—A longitudinal study - Skibinska, Maria; Rajewska-Rager, Aleksandra; Dmitrzak-Weglarz, Monika; Kapelski, Pawel; Lepczynska, Natalia; Kaczmarek, Mariusz; Pawlak, Joanna (Frontiers in Psychiatry, 2022)
Bipolar disorder (BD) is one of the most disabling psychiatric illnesses. Over half of BD patients experienced early onset of the disease, and in most cases, it begins with a depressed mood episode. Up to 50% of adolescents initially diagnosed with major depressive disorder (MDD) convert to bipolar spectrum disorder. Diagnostic tools or biomarkers to facilitate the prediction of diagnosis conversion from MDD to BD are still lacking. Our study aimed to find biomarkers of diagnosis conversion in young patients with mood disorders. We performed a two-year follow-up study on 69 adolescent patients diagnosed with MDD or BD. The control group consisted of 31 healthy youths. We monitored diagnosis change from MDD to BD. Impulsiveness was assessed using Barratt Impulsiveness Scale (BIS-11) and defense mechanisms using Defense Style Questionnaire (DSQ-40). According to the immunological hypothesis of mood disorders, we investigated baseline cytokines levels either in depressive or hypomanic/manic episodes. We correlated interleukin 8 (IL-8) and Tumor Necrosis Factor-alpha (TNF-alpha) levels with clinical factors. We detected higher IL-8 and TNF-alpha in patients in hypomanic/manic compared to depressed episodes. We found correlations of cytokine levels with immature defense style. We did not discover predictors of diagnosis conversion from MDD to BD.